1999
DOI: 10.1007/bf02468390
|View full text |Cite
|
Sign up to set email alerts
|

Filtration convection in a high-frequency vibration field

Abstract: Convection in a porous medium under nonisothermal conditions occurs widely in nature and engineering and is of interest, for example, for studies of the operation of thermal insulators made of porous materials, which are used in modern equipment both under earth conditions and in space studies. In this connection, it makes sense to study the effect of various factors on filtration convection from the viewpoint of controlling the stability of convective flows in a porous medium. One of these factors is the vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…However, in our problem, high-frequency vibrations cause very large accelerations, making it necessary to consider this non-stationary term [6].…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our problem, high-frequency vibrations cause very large accelerations, making it necessary to consider this non-stationary term [6].…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…In the case of a horizontal porous layer saturated by a pure fluid, heated from below or from above Zenkovskaya et al [6] and Bardan et al [7] used the Darcy model including the non-stationary term and adopted the timeaveraged equations formulation to study the influence of high-frequency and small-amplitude vibrations on the onset of convection. They found that vertical vibrations stabilize the rest solution.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of convection in a region of fluid saturating a porous medium subjected to high-frequency vibration of arbitrary direction has been examined by Zenkovskaya [12,13] using the averaging method. Malashetty and Padmavathi [14] asymptotically analyzed the linear stability of a horizontal fluid-saturated porous layer heated from below for the case of small-amplitude gravity modulation.…”
Section: Effect Of Vertical Modulation On Filtration Convection 489mentioning
confidence: 99%
“…Zenkovskaya and Rogovenko [6] and Govender [7] have investigated the effect of vertical vibration on the onset of convection in a Darcian porous layer subject to high frequency and low-amplitude vibrations respectively. Recently, Strong [8] reported the results of this problem for arbitrary range of modulation parameters by the use of continued fraction method.…”
Section: Introductionmentioning
confidence: 99%